2013
DOI: 10.1063/1.4828367
|View full text |Cite
|
Sign up to set email alerts
|

Optimizations of photovoltaic cells including the minimization of internal heat sources

Abstract: International audienceA new approach is introduced and illustrated for optimizing the performances of photovoltaic cells. A thermal criterion, the minimization of the internal heat sources, is added to the usual criteria that consist of minimizing the optical and electrical losses. A proof of concept is delivered by means of modeling in the case of a standard crystalline silicon (cSi) cell for which the dependence on temperature of optical, electrical, and thermal properties is well known. A numerical code nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Recently, Dupré and Vaillon [8] tried to quantify, by simulation, the potential of reducing internal heat source for PV cells as a function of photon electricity generation, cell thickness, and cell heat exchange to its boundary condition. They concluded that increasing the cell thickness can improve both optical and electrical performances, simultaneously reducing heat as well.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Dupré and Vaillon [8] tried to quantify, by simulation, the potential of reducing internal heat source for PV cells as a function of photon electricity generation, cell thickness, and cell heat exchange to its boundary condition. They concluded that increasing the cell thickness can improve both optical and electrical performances, simultaneously reducing heat as well.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that a thermal management system with a high heat transfer coefficient of 10 5 Wm −2 K −1 was required to maintain the cell at room temperature for nanometer-size gaps in order to obtain performances similar to those of Park et al It is thus clear that accounting for the three loss mechanisms is a critical component of the design of optimal nano-TPV power generators. Indeed, Dupré and Vaillon 32 proposed a novel approach for optimizing the performance of standard crystalline silicon solar cells by minimizing radiative and electrical losses as well as thermal losses that are usually omitted. It was shown that the cell architecture leading to a maximum power output is affected when thermal losses are considered in the optimization procedure.…”
mentioning
confidence: 99%